RIWAYAT USIA PERTAMA MENARCHE ≤12 TAHUN BERHUBUNGAN DENGAN KEJADIAN KANKER PAYUDARA PADA WANITA USIA SUBUR - Ariana, Siwi; Budijitno, Selamat; Suhartono, Suhartono (Universitas Tribhuwana Tunggadewi, 2020)
Breast cancer is a continuous cell growth that spreads without control in breast tissue. Young women especially those who are in reproductive ages with breast cancer tend to have more malignant cancer and worse prognosis. The purpose of this study is to prove history of first age menarche ≤12 years associated with the incidence of breast cancer in reproductive ages. Research design analytic observational study used a control case study design. The population in this study were reproductive women aged 15-49 years who were examined at the Oncology clinic in Tugurejo General Hospital with anatomical pathology results. The samples in this study were 42 cases and 42 controls with consecutive sampling technique. The data were analyzed univaraiate anda bivariate by chi-square. Results research history of first age menarche ≤12 years releted of breast cancer with value p= 0,005; OR= 4,015; 95% CI= 1,618-9,966. Conclusion history of the first age of menarche ≤12 years is related to the incidence of breast cancer in women of childbearing age. The researchers can add new variables about risk factors for breast cancer.